Actor/Actant-Network Theory as Emerging Methodology for Environmental Education Research in Southern Africa - Godwell Nhamo (Environmental Association of Southern Africa, 2006)
This paper deliberates on actor/actant-network theory (AANT) as methodology for policy research in environmental education (EE). Insights are drawn from work that applied AANT to research environmental policy processes surrounding the formulation and implementation of South Africa's Plastic Bags Regulations of 2003. The paper reveals that the application of AANT methodology made it possible to trace relationships, actors, actants and actor/actant-networks surrounding the Plastic Bags Regulations as quasi-object (token). The methodology also enabled a focus on understanding and investigating tensions, debates and responses emerging from the policy process. The findings were that after the promulgation of the first draft of the Plastic Bags Regulations in May 2000, tensions emerged around the nature of regulation (whether to use the command and control approach - preferred by Organised Government - or self regulation - preferred by Organised Business and Organised Labour). From these findings, a series of conceptual frameworks were drawn up as identified around key actors and actor/actant-networks. The conceptual frameworks included among them, Organised Government, Organised Business and Organised Labour.